Promoting Social Sustainability through Metaverse Usage in Higher Education: An Examination of Knowledge Management Factors and Students' Perceptions - AL MESMARI, SALEIMAH MOBARAK (2024)
The study mainly focuses on evaluating the current status of the of the metaverse technology application in the education in general and within the UAE Higher education will be presented. The main aim of this research is to provide a comprehensive model for understanding the actual use of metaverse technology and to explore the subsequent impact on social sustainability within UAE HEIs.The objectives of this research are to review the existing literature on metaverse technology in higher education, identifying key factors that have been utilized to understand its adoption and usage. To develop an integrated research model that combines the TPB and T-EESST theories with knowledge management factors, privacy and security concerns, and metaverse-related factors. To empirically validate the developed integrated model using a hybrid Structural Equation Modelling and Artificial Neural Network (SEM-ANN) approach, ensuring a robust analysis of the relationships between the identified factors and students' actual usage behaviour of metaverse platforms in educational settings. This study has selected the quantitative technique over the other research approaches for the two main reasons. The first reason is because of the nature of the study. In this study, the theories have been tested by formulating precise hypotheses, and then gathered numerical data to prove or disprove those hypotheses. Statistical methods are utilised in order to do the analysis on the collected data. The findings of PLS-SEM show that factors such as attitude, knowledge acquisition, sharing, application, protection, immersion, presence, perceived security, and privacy play crucial roles in the usage of a system or technology. However, subjective norm, perceived behavioural control, and knowledge storage capabilities are not significant determinants of use. Importantly, the use of Metaverse is found to have a substantial positive impact on social sustainability, highlighting the importance of these factors in promoting sustainable social outcomes through Metaverse usage. The ANN analysis results align with the PLS-SEM findings, confirming the significant impact of factors like Knowledge Sharing, Knowledge Application, Presence, and Perceived Security on Metaverse use and its contribution to social sustainability. In this study, a number of practical implications offered that should be taken into account by metaverse platform decision-makers, administrators, developers, and educators in the field of higher education. The findings of this research provide valuable insights for developers and practitioners in the development and design of metaverse platforms for higher educational institutions, as they could examine the possible knowledge management aspects identified in this research. hese studies uncover distinct challenges and opportunities, providing a deeper understanding of the technology's applications and implications in diverse contexts.